An Analysis of Feminism Depicted in She's The Man Film by Andy Fickman - Winar Gumilang Afandi Putri; Masulah -; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2015)
This study took She’s The Man film as the study object because it shows how did one of the unfair condition happen. Aims of this study are to find out characterizations of Viola Hastings in She’s The Man film and to analyze how is Viola Hastings’ characterizations reflected feminism. Some theories that was applied in this study were characterization and feminism theories. To reach the aims, the writer used descriptive qualitative as the method. For the primary data the writer took script of She’s The Man film directed by Andy Fickman. The result of this study are the descriptions of physical appearance of the main character, personality of the main character and social relationship of the main character. Then, the writer analyzed how her characterizations reflected feminism. Charaterizations of Viola were hated sexist and tomboy because tomboy indicated Viola was a girl who strong and brave. It is different from the most people thought about girls whom weak and spoiled. She hated sexist so much, it means she did not like if there is people underestimate girls. Viola proved that gender did not influence anything and she could win her game, beating Cornwall boys team because of her hard training.